Cerebral Cavernous Malformation: From Genetics to Pharmacotherapy - Zhuangzhuang Zhang; Jianwen Deng; Weiping Sun; Zhaoxia Wang (Brain and Behavior)
ABSTRACT Introduction Cerebral cavernous malformation (CCM) is a type of cerebrovascular abnormality in the central nervous system linked to both germline and somatic genetic mutations. Recent preclinical and clinical studies have shown that various drugs can effectively reduce the burden of CCM lesions. Despite significant progress, the mechanisms driving CCM remain incompletely understood, and to date, no drugs have been developed that can cure or prevent CCM. This review aims to explore the genetic mutations, molecular mechanisms, and pharmacological interventions related to CCM. Methods Literatures on the genetic mechanisms and pharmacological treatments of CCM can be searched in PubMed and Web of Science. Results Germline and somatic mutations mediate the onset and development of CCM through several molecular pathways. Medications such as statins, fasudil, rapamycin, and propranolol can alleviate CCM symptoms or hinder its progression by specifically modulating the corresponding targets. Conclusions Understanding the molecular mechanisms underlying CCM offers potential for targeted therapies. Further research into novel mutations and treatment strategies is essential for improving patient outcomes.